Cowpea mosaic virus for material fabrication addressable carboxylate groups on a programmable nanoscaffold - Steinmetz, Nicole F (Langmuir : the ACS journal of surfaces and colloids, 2006)
For the first time, decoration of surface-exposed carboxylate groups on Cowpea mosaic virus particles is reported, thus increasing the number and types of addressable surface groups on this nanoscaffold. First, the addressabilty of carboxylates was demonstrated using a carboxylate-selective fluorescent dye, N-cyclohexyl-N'-(4-(dimethylamino)naphthyl)carbodiimide. Second, it was shown that the virions can be decorated with approximately 180 redox active, methyl(aminopropyl)viologen moieties by coupling to the surface carboxylates. The display of multiple redox centers on the virus particle surface may lead to the development of novel electron-transfer mediators in redox catalysis, to biosensors, and to nanoelectronic devices such as molecular batteries